2009
DOI: 10.1007/s11483-009-9137-4
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Generation Microscopy: A Tool for Spatially and Temporally Resolved Studies of Heat Induced Structural Changes in Meat

Abstract: Myofibers and collagen show non-linear optical properties enabling imaging using second harmonic generation (SHG) microscopy. The technique is evaluated for use as a tool for real-time studies of thermally induced changes in thin samples of unfixed and unstained pork. The forward and the backward scattered SHG light reveal complementary features of the structures of myofibers and collagen fibers. Upon heating the myofibers show no structural changes before reaching a temperature of 53°C. At this temperature th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…indicated that the first decrease in G ′ was mainly because of rising temperature, which destroyed the hydrogen bonds. Brüggemann et al . showed that the characteristic peak of myosin almost disappeared at 53 °C, which was indicative of protein denaturation.…”
Section: Resultsmentioning
confidence: 99%
“…indicated that the first decrease in G ′ was mainly because of rising temperature, which destroyed the hydrogen bonds. Brüggemann et al . showed that the characteristic peak of myosin almost disappeared at 53 °C, which was indicative of protein denaturation.…”
Section: Resultsmentioning
confidence: 99%
“…According to the DSC results, Kijowski and Mast () observed that there was one major peak temperature of thermal shrinkage of connective tissue at 65.3°C and some minor thermal transitions at temperatures lower than 65.3°C. Using Second Harmonic Generation microscopy, Bruggemann et al () reported that the structural changes in collagen mainly occurred at 57−61°C. Accordingly, most of the collagens in this study were denatured at 80°C, thus leading to the non‐significant difference in collagen solubility between the treatments.…”
Section: Resultsmentioning
confidence: 99%
“…At 58 °C the tenderization could be achieved at a clearly lower heating time. This is probably due to the fact that collagen alteration mainly occurs at this temperature (Brüggemann, Brewer, Risbo, & Bagatolli, 2010;Christensen et al, 2011b;Christensen et al, 2013). Christensen et al (2013) is only marginal.…”
Section: Shear Forcementioning
confidence: 95%